Chase's annual events : 1994. (Chicago, Ill. : Contemporary Books, 1994)
The electronic version contains the complete print version including multiple tables, enhanced functionality, complete text of the paper index, Boolean searching, scheduling, new groupings, not in the print edition, and networkability. This version offers more complete access to the information than the print version is able offer.
Vols. for 1998- include also a CD-ROM version of this publication.
Vols. for 1998- are housed in SFRR. $5 DLC.
Vols. for 1995- called also 38th- year of publication.
System requirements for accompanying CD-ROM: IBM-compatible PC with Windows 3.x or Windows 9.5' CD-ROM drive; mouse.
Latest issue consulted: 2015.
SERBIB/SERLOC merged record
Keywords: National holidays; Holidays -- United States -- Periodicals; Holidays -- Periodicals; Almanacs as Topic; Holidays; Holidays; United States; Periodicals; Calendars